Sustained Improvement in Neonatal Intensive Care Unit Safety Attitudes After Teamwork Training. Issue 3 (September 2018) - Murphy, Thomas; Laptook, Abbot; Bender, Jesse
Abstract : Objectives: This study aimed to measure safety attitudes in the neonatal intensive care unit (NICU) before and serially after a compulsory, multidisciplinary teamwork and communication training initiative and novel sustainment program. Methods: Training was administered to NICU staff and subsequent sustainment efforts were directed at enculturating core principles over the following year. A modified Agency for Healthcare Research and Quality Survey on Patient Safety Culture was administered before as well as 3 and 12 months after training. Longitudinal survey results were compared with the national Agency for Healthcare Research and Quality survey data. Results: Ninety-six percent of 350 NICU staff were trained over 2 months. Survey response rates were 84%, 71%, and 83% before, at 3 months, and at 12 months after training, respectively. Items with sustained improvement pertained to staff empowerment and patient hand-offs. The proportion of participants who agreed with the statement, "Staff feel free to question the decisions or actions of those with more authority" increased from 55% to 76% and 83% at 3 and 12 months, respectively ( P < 0.0001). The proportion of participants who disagreed with the statement, "Things 'fall between the cracks' when transferring patients from one unit to another" increased from 36% to 48% and 52% at 3 and 12 months, respectively ( P < 0.01). The only significant decline was for the statement, "We are actively doing things to improve patient safety." The proportion of respondents who agreed dropped from 93% to 83% at 3 months ( P = 0.02). Conclusions: A novel sustainment program after teamwork and communication training measurably improved most staff safety attitudes over 1 year.